Bio-Based Materials: Contribution to Advancing Circular Economy (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on studies dealing with bio-based materials and its contribution to a circular economy. Research dealing with recycling, waste conversion to bio-based products, the development of bio-based composites, and surface treatments on cellulose fibres have been included in this reprint.